The Effect of the Addition of Citrus Fruits Juice on The Physical and Chemical Characteristics of Sapodilla (Manikara zapota) Sliced Jam - Sayuti, Kesuma; Mutiara, E P; Silvy, D (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
This study aims to determine the effect of various citrus fruit juices on the qualities of sliced sapodilla jam. Completely randomized design (CRD) with four treatments and four replications. A (2% citric acid) served as the control, B (26% lime juice), C (26% lemon juice), and D (26% kaffir lime juice) were the treatments. The data were statistically examined using ANOVA and Duncan's New Multiple Range Test (DNMRT) at the 5% significance level. The addition of citrus fruit juice had a substantial influence on the jam's folding test, total titrated acid, pH value, water content, ash content, total dissolved solids, total sugar, crude fiber, and vitamin C did not affect its water activity. According to the chemical features, the addition of lime juice as a source of citric acid resembles the characteristics of sheet jam made with pure citric acid more closely.